REVIEW ON TEN DISSERTATIONS WITH RESPECT TO TEACHING AND LEARNING ENGLISH IN ACOMPARATIVE PERSPECTIVE - Fauzan M.Pd. (The Center for Language Development, Mataram State Islamic University., 2016)
Abstract: This study aims to analyze the diffrences and similarities of ten distinct research on the area of L2, whose parts such as problem formulation, method, result and discussion are compared. The result shows that four out of the ten problem formulations and results of the dissertations have a lot in common. This includes dissertations 4, 6, 8, and 10 which are better as they are more explicit and use logical rationales. Three of the ten dissertations have similarities in terms of title written structure and are worse than the rests because they are longer. The dissertations 2, 3, 4, 5, 6, 8 and 9 share similarities in terms of background or rationales for the studies and are better as they employ relevant studies. The dissertations 3, 4, 5, 6, 8, and 9 are similer in terms of literature review and are better than 1, 2, 7, and 10 as they are more adequate and relevant to the studies. In the aspect of methodology, dissertations 3, 4, 5, 6, 8, and 9 have similarities but are different from dissertations 1, 2, 7, and 10, because the components of the research methodology of the former are more explicit than those of the latter. In terms of discussion section, there are similarities am ong dissertations 2, 3, 8, 9, and 10 but different from the dissertations 1, 4, 5, 6, and 7. The former entail chapters of discussions which support the finding with related theories. This study is hoped to contribute to the betterment of research writing and recommends that another future study employing, for example, meta analysis procedure.